Bibliometric analysis on the integration of Last-Mile Logistics with Industry 4.0 - Oliveira, Kévila Camilla Santos de; Tavares, Dalton Matsuo; Bachega, Stella Jacyszyn (Brazilian Journal of Production Engineering, 2026)
Last Mile Logistics (LML) represents the final stage of a Business to Consumer (B2C) service, delivering goods to the intended customers. Some challenges of the logistics process can be overcome using Industry 4.0 tools and technologies. This article aims to identify, through bibliometric analysis, the scientific production that links LML and Industry 4.0 from 2021 to 2025, examining the authors, collaboration networks, and trends of emerging research themes. To this end, the hypothetico-deductive scientific method was applied, along with a mixed qualitative and quantitative research approach and the bibliometric analysis procedure using the VOSviewer software. The investigation used the ScienceDirect database. The publication pattern within the analyzed time horizon was examined using term co-occurrence techniques and cluster analysis. The results indicate that most research associated with IoT, big data, and autonomous vehicles is dedicated to LML. This suggests the importance of these technologies for optimizing deliveries. This study presents the scientific landscape and provides support for proposing theoretical–conceptual models and practical solutions in the logistics field.
Keywords: Last-Mile logistics; Industry 4.0; Bibliometric analysis; VOSviewer